Investigation of influence of elbow on pump inlet flow behaviour in cavitating flow. (July 2022) - Yousaf, Bilal; Manzoor, Tareq; Qaisrani, Mumtaz A.; Khan, Ijaz; Sana Ullah Sahar, M; Tahir, Waqas
Highlights: Effect of elbows is considered in downstream region of pipe and pumps inlets. Numerical simulations for different curvature elbows were carried out. Pressure at impeller of pump drops down that cause cavitation. The variations in the velocity near downstream was uneven. Effect of cavitation in an elbow is affected by curvature of elbow. Abstract: This paper discusses the effect of elbows in the downstream region of pipe and pumps inlet flow conditions according to standards. Cavitation is a significant occurrence in such types of flow regimes that causes erosion and ultimately affects the pump's performance. Cavitation is also investigated using computational analysis using ANSYS Fluent. It is concluded that the elbow with 90° angle in pipe with some curvature produce eddies in the fluid flow. The variations in the velocity near the downstream were uneven. Moreover, it is also determined computationally that the effect of cavitation on pump inlet flow conditions is also high and in increasing trend. The effect of cavitation in an elbow pipe can be increased if the curvature of the elbow is reduced. This ultimately effect the performance of the pump.